Increased Thromboembolic Events With Dabigatran Compared With Vitamin K Antagonism in Left Ventricular Assist Device Patients: A Randomized Controlled Pilot Trial. (May 2017) - Andreas, Martin; Moayedifar, Roxana; Wieselthaler, Georg; Wolzt, Michael; Riebandt, Julia; Haberl, Thomas; Angleitner, Philipp; Schlöglhofer, Thomas; Wiedemann, Dominik; Schima, Heinrich; Laufer, Guenther; Zimpfer, Daniel
Abstract : Background—: Left ventricular assist device–supported patients are usually anticoagulated with a combination of aspirin and vitamin K antagonists. Long-term vitamin K antagonist therapy can be complicated by unstable international normalized ratio values and patient-related compliance problems. Therefore, direct thrombin inhibitors may represent an alternative to vitamin K antagonists. Methods and Results—: Thirty HeartWare ventricular assist device patients with stable renal function were planned for this prospective, randomized, open-label, single-center study. Patients were randomized to receive either phenprocoumon or dabigatran in addition to aspirin for long-term anticoagulation. Treatment duration was scheduled for 1 year and stopped after observation of a primary end point. Dabigatran dose was 110 and 75 mg BID in patients with normal or impaired renal function (glomerular filtration rate >80 mL/min or between 80 and 30 mL/min, respectively). The study was stopped prematurely for safety reasons after 16 patients (61±8 years, 1 female) were randomized. Thromboembolic events occurred in 4 subjects receiving dabigatran (50%) and in 1 receiving phenprocoumon (13%; P =0.28). No major bleeding was recorded, and no patient died during the study. Median time to treatment termination was significantly shorter in dabigatran patients (8.5 versus 12.0 months; P =0.015). Conclusions—: Thromboembolic events on dabigatran led to early termination of a randomized controlled trial of dabigatran versus phenprocoumon in left ventricular assist device patients. Clinical Trial Registration—: https://www.clinicaltrials.gov . Unique identifier: NCT02872649. Abstract : Supplemental Digital Content is available in the text.